Curved trapezoidal Cu3P/NiCoP nanosheet arrays on nickel-cobalt foam for pH-insensitive hydrogen evolution reaction. (20th July 2022) - Yang, Yaoxia; Zhang, Lan; Guo, Fengyao; Kang, Mi; An, Xuqin; Jiang, Nana; Wang, Qingqing; Ma, Lanxin; Yang, Zhiwang; Lei, Ziqiang
Abstract: The rational design and controllable manufacture of electrocatalyst for pH-insensitive hydrogen evolution reactions (HER) based on the abundant elements of the earth is a critical, urgent and challenging task. Herein, a curved trapezoidal nanosheet structure on conductive Ni-Co support (Cu3 P/NiCoP/NCF) was designed and fabricated as a novel electrocatalyst for HER, benefiting from the synergism effect between Cu3 P and NiCoP phases, the optimal electronic structure, the intrinsic low resistance of the bimetal substrate and the uniform trapezoidal nanosheet structure. The self-supported Cu3 P/NiCoP/NCF composite catalyst exhibits excellent electrocatalytic performance for HER in a wide pH range with the overpotentials of 51 mV, 87 mV, and 151 mV at the current density of 10 mA cm −2 in alkaline, acidic and neutral electrolytes, respectively. Impressively, the fabricated Cu3 P/NiCoP/NCF catalyst shows ultra-stable electrocatalytic performance and good durability in HER processes. What's more, the Cu3 P/NiCoP/NCF could achieve a high current density of at least 300 mA cm −2 in alkaline. This innovative combination of the approach is expected to contribute a feasible strategy to the cause of human energy progress and is promising well beyond the water electrolysis field.